A drug screening to identify novel combinatorial strategies for boosting cancer immunotherapy efficacy - Zongliang Zhang; Guoqing Wang; Kunhong Zhong; Yongdong Chen; Nian Yang; Qizhong Lu; Boyang Yuan; Zeng Wang; Hexian Li; Liping Guo; Ruyuan Zhang; Zhiguo Wu; et al. (Journal of Translational Medicine, 2023)
Abstract Background Chimeric antigen receptor (CAR) T cells and immune checkpoint blockades (ICBs) have made remarkable breakthroughs in cancer treatment, but the efficacy is still limited for solid tumors due to tumor antigen heterogeneity and the tumor immune microenvironment. The restrained treatment efficacy prompted us to seek new potential therapeutic methods. Methods In this study, we conducted a small molecule compound library screen in a human BC cell line to identify whether certain drugs contribute to CAR T cell killing. Signaling pathways of tumor cells and T cells affected by the screened drugs were predicted via RNA sequencing. Among them, the antitumor activities of JK184 in combination with CAR T cells or ICBs were evaluated in vitro and in vivo. Results We selected three small molecule drugs from a compound library, among which JK184 directly induces tumor cell apoptosis by inhibiting the Hedgehog signaling pathway, modulates B7-H3 CAR T cells to an effector memory phenotype, and promotes B7-H3 CAR T cells cytokine secretion in vitro. In addition, our data suggested that JK184 exerts antitumor activities and strongly synergizes with B7-H3 CAR T cells or ICBs in vivo. Mechanistically, JK184 enhances B7-H3 CAR T cells infiltrating in xenograft mouse models. Moreover, JK184 combined with ICB markedly reshaped the tumor immune microenvironment by increasing effector T cells infiltration and inflammation cytokine secretion, inhibiting the recruitment of MDSCs and the transition of M2-type macrophages in an immunocompetent mouse model. Conclusion These data show that JK184 may be a potential adjutant in combination with CAR T cells or ICB therapy.